Screening of larval/pupal P-element induced lethals on the second chromosome in Drosophila melanogaster: clonal analysis and morphology of imaginal discs. - Roch, F.; Serras, F.; Cifuentes, F.J.; Corominas, M.; Alsina, B.; Lopez-Varea, A.; Hernandez, R.; Guerra, D.; Cavicchi, S.; Baguna, J.; Garcia-Bellido, A. (Molecular and General Genetics, 1998)
We have carried out screens for lethal mutations on the second chromosome of Drosophila melanogaster that are associated with abnormal imaginal disc morphologies, particularly in the wing disc. From a collection of 164 P element-induced mutations with a late larva/pupa lethal phase we have identified 56 new loci whose gene products are required for normal wing disc development and for normal morphology of other larval organs. Genetic mosaics of these 56 mutant lines show clonal mutant phenotypes for 23 cell-viable mutations. These phenotypes result from altered cell parameters. Causal relationships between disc and clonal phenotypes are discussed.